Mechanical behavior of in vivo degraded second generation resorbable magnesium scaffolds (RMS). (March 2019) - Brandt-Wunderlich, Christoph; Ruppelt, Philipp; Zumstein, Philine; Schmidt, Wolfram; Arbeiter, Daniela; Schmitz, Klaus-Peter; Grabow, Niels
Abstract: Resorbable magnesium scaffolds are used for the treatment of atherosclerotic coronary vascular disease and furthermore, for vascular restoration therapy. Recently, the first-in-man clinical studies with Magmaris showed promising results regarding the target lesion failure as well as vasomotion properties after 12 and 24 month. The consistency of in vivo degraded magnesium alloys in a cardiovascular environment is qualitatively described in literature, but only little has been disclosed about the actual change in mechanical properties and the behavior of the magnesium alloy degradation products. In the present study, uncoated magnesium scaffolds 3.0 × 20 mm were implanted in coronary arteries of two healthy Goetinnger mini-swine. The scaffolds were explanted to evaluate the mechanical properties of the degraded magnesium scaffolds after 180 days in vivo. Ex vivo sample preparation and test conditions were adapted to a customized compression test setup which was developed to investigate the micro-scale scaffold fragments (width 225 ± 75 µm, thickness 150 µm). As reference bare undegraded magnesium scaffold fragments were tested. Mechanical parameters relating to force as a function of displacement were determined for both sample groups. The undegraded samples showed no fracturing at the maximum applied force of 8 N, whereas the in vivo degraded test samples showed forces of 0.411 ± 0.197 N at the first fracturing and a maximum force of 0.956 ± 0.525 N. The deformation work, calculated as area beneath the force-displacement curve, of the in vivo degraded test samples was reduced by approximately 87–88% compared to the undegraded samples (5.20 mN mm and 40.79 mN mm, both at 7.5% deformation). The indication for a complete loss of structural integrity through a reduction of mechanical properties after a certain degradation time increases the chance to restore vascular function and physiological vasomotion in the stented vessel compartment.